The Concept of Shuffah at the Masjid Nabawi: Inspiration for the Revitalization of Education Throughout the Ages - Shobaruddin, Dudin; Wahyono, Zubaidi (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
The Masjid Nabawi, beyond its primary role as a place of worship, has historically served as a dynamic center of education, civilization, and community development, particularly through the Shuffah model. The Shuffah, inhabited by Ahl al-Shuffah who dedicated themselves to religious learning, became the earliest prototype of mosque-based education, integrating spiritual, intellectual, and social dimensions. This model not only produced companions with deep knowledge and piety but also laid the foundation for the scholarly traditions that flourished in subsequent centuries. Using a qualitative descriptive approach and a literature review, this study explores the educational significance of the Shuffah and its relevance to contemporary Islamic education. The findings indicate that the Shuffah emphasizes holistic learning, moral character formation, and community empowerment—principles highly applicable to modern challenges such as globalization, moral decline, and educational stagnation. The research argues that revitalizing mosques as comprehensive centers of education, inspired by the Prophet's model, can significantly contribute to the development of character, intellectual resilience, and socio-economic empowerment in Muslim societies. Thus, restoring the prophetic function of mosques aligns with the broader Islamic vision of producing knowledgeable, ethical, and socially responsible generations capable of contributing positively to global civilization.